Reduction of ration with protein increase in Clarias gariepinus - LLanes, J.; Toledo, J.; Sarduy, Lucía (Cuban Journal of Agricultural Science, 2017)
A total of 225 young fish of Clarias gariepinus (10.1+0.01g initial average weight) were randomly distributed in three triplicate treatments according to the simple classification model, with the purpose of evaluating the productive performance of these fishes, by reducing the amount of ration and increase dietary protein levels. The treatments consisted of three diets with 34.7, 39.2 and 43.7% of crude protein added at 8.0, 7.0 and 6.4% of body weight / day so that all fishes received 2.8 g of crude protein / kg live weight /day. The supplied feed did not significantly differ (P> 0.05) between treatments (44.3, 44.9 and 45.3 g/fish). However, significant differences were found in supplied CP (16.1, 18.0 and 20.4 g / fish), the growths (39.4, 47.8 and 59.1 g of average weight) and feed conversion (1.5, 1.2 and 0.9), in favor of increasing dietary protein levels. The economic analysis showed differences in the rations cost (US 0,857, 0,977 and 1.088 / kg), but lower amounts in the production of 1kg of live weight (US 1,285, 1,172 and 0.979 / kg). It was demonstrated that the reduction of the amount of ration with increase of dietary protein improved the productive performance of Clarias gariepinus with positive economic effect. Key words: feeding, clarias, protein requirement.